1986
DOI: 10.1128/iai.53.2.312-316.1986
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characteristics of collagenolytic enzyme produced by Candida albicans

Abstract: In media containing collagen as the nitrogen source, the pathogenic yeast Candida albicans secreted a collagenolytic enzyme. Purification of the enzyme from a culture filtrate was achieved by DEAE-Sephacel chromatography at pH 6.7. The molecular weight was found to be 46,000 by 10% sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and the isoelectric point was at pH 4.2. The pH optimum lay between 3.5 and 4.0, and above pH 6.0, the enzyme underwent alkaline denaturation. The enzyme was heat labile, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
7

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 18 publications
2
33
0
7
Order By: Relevance
“…The results of this study revealed a significant reduction in the quantity of C. albicans adhering to the surfaces demineralized by the decalcifying agents in G3 (NaOCl + EDTA), G4 (NaOCl + PAA) and G5 (NaOCl + HEDP). These results reinforce that this microorganism can use the dentine as a source of nutrition (Sen et al 1997b) by digesting the collagen (Kaminishi et al 1986, Hagihara et al 1988) and releasing the calcium necessary for their calcium-dependent surface proteins with adherence activity (Klotz et al 1993). The final flushes with CHX reduced the quantity of cells adhered in G6 (NaOCl + EDTA + CHX), G7 (NaOCl + PAA + CHX) and G8 (NaOCl + HEDP + CHX) compared with G3 (NaOCl + EDTA), G4 (NaOCl + PAA) and G5 (NaOCl + HEDP); however, there were no significant differences amongst all these groups.…”
Section: Discussionsupporting
confidence: 77%
“…The results of this study revealed a significant reduction in the quantity of C. albicans adhering to the surfaces demineralized by the decalcifying agents in G3 (NaOCl + EDTA), G4 (NaOCl + PAA) and G5 (NaOCl + HEDP). These results reinforce that this microorganism can use the dentine as a source of nutrition (Sen et al 1997b) by digesting the collagen (Kaminishi et al 1986, Hagihara et al 1988) and releasing the calcium necessary for their calcium-dependent surface proteins with adherence activity (Klotz et al 1993). The final flushes with CHX reduced the quantity of cells adhered in G6 (NaOCl + EDTA + CHX), G7 (NaOCl + PAA + CHX) and G8 (NaOCl + HEDP + CHX) compared with G3 (NaOCl + EDTA), G4 (NaOCl + PAA) and G5 (NaOCl + HEDP); however, there were no significant differences amongst all these groups.…”
Section: Discussionsupporting
confidence: 77%
“…The yeasts, enteric rods, or pseudomonads isolated in the present study are pathogens in various medical infections (9,49,79), and possess an array of virulence factors of possible relevance to periodontal disease (69). For example, C. albicans can invade sulcular epithelium and gingival connective tissues (3,16,20), inhibit PMN functions (29), kill monocytes (15), degrade alpha-2-macroglobulin (58,59), procedure collagenase (33), phospholipases (53), aminopeptidases (46), acid and alkaline phosphatases (13) keratin protease (24), and TgGl, IgAl, and IgA2 immunoglobulin proteases (58,59).…”
Section: Discussionmentioning
confidence: 94%
“…However, clinical itnprovetnent has been observed following antitnycotic treatment (3,4,10). In spite of the very small nutnerical proportion of yeasts in denture plaque, and the lack of correlation between stomatitis and yeast quantities in some studies (5,36), yeasts must, therefore, still be considered important opportunistic pathogens in denture-induced stotnatitis (3,4,9,10,13,22), In Candida albicans and to less ex-tent in other yeast species, several virulenee factors have been demonstrated //; vitro, notably phospholipase (35), and acidic proteinases capable of degrading keratin (16,25), collagen (18), serum albumin (8), saliva proteins (32), itnmunoglobulins Gl, Al and A2, and alpha-2-macroglobulin (29,30). There are strain differences in these enzymes, and their production and activity depends on the growth conditions (29), It is not known to what extent they are active in denture plaque.…”
Section: Discussionmentioning
confidence: 99%